An experimental study on aviation kerosene pool fire flame and thermal radiation. Issue 1 (1st April 2022) - Wei, Ruichao; Wang, Baowei; He, Qize; Lian, Liping; Huang, Shenshi
Abstract: In this study, small-scale aviation kerosene pool fire experiments were carried out. The experiments were conducted by measuring the flame temperature and plume temperature on the axis by thermocouples and obtaining 50% of the flame intermittency height from the images taken by the camera. Using the Heskestad's model, the fitting result of flame height and pan size was obtained. Moreover, the surface emission power of aviation kerosene flame was calculated based on the cylindrical flame theory. The experimental data in this paper will contribute to studies of aviation kerosene fire simulations.